2018
DOI: 10.1002/pbc.26993
|View full text |Cite
|
Sign up to set email alerts
|

Nephrin as a biomarker of sickle cell glomerulopathy in Malawi

Abstract: These data suggest that a substantial number of children with SCD in Malawi have renal disease and could be at risk for worsening nephropathy and ESRD as they age. Our data suggest that urinary nephrin could be utilized as an early marker of glomerular disease in SCD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…Table 3. Biomarkers investigated for use in sickle cell nephropathy Proposed potential markers for early detection and monitoring progression of SCN Urine microalbumin/creatinine ratio Urine total protein/creatinine ratio Urine N-acetyl-beta-D-glucosaminidase (NAG) [24,89] Urine kidney injury molecule-1 [24,89] Urine ceruloplasmin [90] Urine free hemoglobin [29] Urine nephrin [91] Plasma soluble FMS-like tyrosine kinase-1 (sFLT-1) [92] Plasma cystatin C [89,93] Measured glomerular filtration rate using iohexol clearance [94] Markers with conflicting or negative data on association with proteinuria in SCN Urine neutrophil gelatinase-associated lipocalin (NGAL) [63,89,95] Urine transforming growth factor beta (TGFβ) [63,89,95] Urine liver-type fatty acid binding protein (L-FABP) [89] Urine endothelin-1 [24] Olaniran/Eneanya/Nigwekar/VelaParada/Achebe/Sharma/Thadhani Non-Pharmacologic Therapies The evidence for the non-pharmacological therapies in SCN is sparse. In particular, chronic blood transfusions early in childhood have been shown to be reno-protective in children [15], but it is not clear how long this effect lasts.…”
Section: Current Therapies For Scn (Table 4)mentioning
confidence: 99%
“…Table 3. Biomarkers investigated for use in sickle cell nephropathy Proposed potential markers for early detection and monitoring progression of SCN Urine microalbumin/creatinine ratio Urine total protein/creatinine ratio Urine N-acetyl-beta-D-glucosaminidase (NAG) [24,89] Urine kidney injury molecule-1 [24,89] Urine ceruloplasmin [90] Urine free hemoglobin [29] Urine nephrin [91] Plasma soluble FMS-like tyrosine kinase-1 (sFLT-1) [92] Plasma cystatin C [89,93] Measured glomerular filtration rate using iohexol clearance [94] Markers with conflicting or negative data on association with proteinuria in SCN Urine neutrophil gelatinase-associated lipocalin (NGAL) [63,89,95] Urine transforming growth factor beta (TGFβ) [63,89,95] Urine liver-type fatty acid binding protein (L-FABP) [89] Urine endothelin-1 [24] Olaniran/Eneanya/Nigwekar/VelaParada/Achebe/Sharma/Thadhani Non-Pharmacologic Therapies The evidence for the non-pharmacological therapies in SCN is sparse. In particular, chronic blood transfusions early in childhood have been shown to be reno-protective in children [15], but it is not clear how long this effect lasts.…”
Section: Current Therapies For Scn (Table 4)mentioning
confidence: 99%
“…1 Albuminuria, which represents an early stage of chronic kidney disease (CKD), starts in childhood and may predict early mortality in SCA. [4][5][6][7][8][9] CKD occurs in ;30% of adult SCA patients and is associated with a higher risk of mortality when resulting from SCA compared with other causes of CKD. 10,11 Once end-stage renal disease (ESRD) is recognized, the 1-year mortality rate is 3 times higher among patients with SCA compared with non-SCA individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, additional crosssectional studies have demonstrated the presence of elevated renal injury biomarkers in young SCD patients. 7,[13][14][15] Elevations in tubular injury markers are associated with glomerular injury, 16 highlighting potential tubular alterations happening prior to glomerulopathy, and suggesting a tubuloglomerular mechanism of kidney injury in SCD. However, critically absent is evidence to demonstrate the characteristics of primary pathophysiological processes involved in kidney injury and the natural course of the renal disease in SCD.…”
Section: Introductionmentioning
confidence: 99%